(untitled) (Bangladesh Journal of Agricultural Research, 2008)
Impacts of participatory variety selection in wheat on agro-economic changes like adoption of new wheat varieties and production technologies, income and attitude change of the wheat farmers, etc. are presented in the paper. Participatory variety selection was conducted at 12 villages of four districts in Bangladesh. Base line information from the villages was collected through participatory rural appraisal and household survey in 2002. Data on agro-economic changes were collected through household survey in 2005. Impacts were assessed from the difference of the data of two surveys. The area of the check variety Kanchan came down from 97.8% (covered in 2002) to 57% in the working villages in 2005. Varietal diversity was increased remarkably and seven varieties were found to cultivate in 2004-05. The new varieties occupied 43% of the wheat areas. Seed preservation by farmers was increased remarkably and 208 tons seeds of new varieties were preserved by them in 2004-05. When 60% seeds of their total requirements were collected from Bangladesh Agricultural Development Corporation in 2002, then, 100% seeds were used from farmers own source in 2004-05. There were remarkable changes in production technology adoption, sources of agricultural knowledge, attitude and income changes. Farmers income was increased to Tk. 11148/ha due to cultivation of new varieties and use of recommended production technologies. Participatory variety selection approach in wheat was found very useful to increase wheat production in the working villages. Widespread use of this approach may be useful throughout the county in other crops also. DOI: http://dx.doi.org/10.3329/bjar.v32i3.462 Bangladesh J. Agril. Res. 32(3) : 335-347, September 2007